Exploring the utility of a novel point‐of‐care whole blood thrombin generation assay following trauma: A pilot study. Issue 3 (8th March 2021) - Ferrara, Michael J.; MacArthur, Taleen A.; Butenas, Saulius; Mann, Kenneth G.; Immermann, Joseph M.; Spears, Grant M.; Bailey, Kent R.; Kozar, Rosemary A.; Heller, Stephanie F.; Loomis, Erica A.; Stephens, Daniel; Park, Myung S.
Abstract: Introduction: Plasma thrombin generation kinetics as measured by the calibrated automated thrombogram (CAT) assay is a predictor of symptomatic venous thromboembolism after trauma. We hypothesized that data from a new prototype assay for measurement of thrombin generation kinetics in fresh whole blood (near patient testing of thrombin generation), will correlate with the standard CAT assay in the same patients, making it a potential tool in the future care of trauma patients. Methods: Patients were enrolled from June 2018 to February 2020. Within 12 hours of injury, blood samples were collected simultaneously for both assays. Variables compared and correlated between assays were lag time, peak height, time to peak, and endogenous thrombin potential. Data are presented as median with interquartile range (IQR). Spearman and Pearson correlations were estimated and tested between both assays; a P value of <0.05 was considered to be significant. Results: A total of 64 trauma patients had samples analyzed: injury severity score = 17 (IQR), 10‐26], hospital length of stay = 7.5 (IQR), 2‐18) days, age = 52 (IQR, 35‐63) years, 71.9% male, and 42.2% of patients received a transfusion within 24 hours of injury. Thrombin generation parameters between plasma and whole blood were compared and found that all parameters of the two assays correlate in trauma patients. Conclusion: In this pilot study, we have found that a novel point‐of‐care whole blood thrombin generation assay yields results with modest but statistically significant correlations to those of a standard plasma thrombin generation assay. This finding supports studying this device in a larger, adequately powered study.